Cross-Sector Collaboration to Improve Access to Community Services for People Living With Diabetes: Contributions From Actor-Network Theory - Géraldine Layani; Alexandre Tremblay; Marie-Thérèse Lussier; Isabelle Godbout; Hélène Bihan; Claire Gosselin; Mégane Pierre; Aude Motulsky; Isabelle Brault; Isabel Rodrigues; Janusz Kaczorowski; Marie-Claude Vanier; et al. (SAGE Publishing, 2024)
Diabetes is a global public health issue. The Public Health Agency of Canada published a Diabetes Framework 2022 which recommends collaborative work across sectors to mitigate the impact of diabetes on health and quality of life. Since 2020, the INMED-COMMUNITY pathway has been implemented in Laval, Québec developing collaboration between healthcare and community sectors through a participatory action research approach. The aim of this article is to gain a better understanding of the INMED-COMMUNITY pathway implementation process, based on the mobilization of network actor theory. Qualitative analysis of semi-structured interviews conducted from January to March 2023 with 12 participants from 3 different sectors (community, health system, research), were carried out using actor-network theory. The results explored the conditions for effective intersectoral collaboration in a participatory action research approach to implement the INMED-COMMUNITY pathway. These were: (1) contextualization of the project, (2) a consultation approach involving various stakeholders, (3) creation of new partnerships, (4) presence of a project coordinator, and (5) mobilization of stakeholders around a common definition of diabetes. Mediation supported by a project coordinator contributed to the implementation of an intersectoral collaborative health intervention, largely due to early identification of controversies.